Determining the canning quality of small seeded white beans (Phaseolus vulgaris L.) - De Lange, Anna Francina (University of the Free State, 1999)
It is important to the producers, processors and consumers in south Africa to have dry bean cultivars with acceptable canning quality. Therefore, dry bean breeders needs sui table screening methods to evaluate the various lines at an early stage (F4) when only small amounts of seed are available. A micro-canning method to evaluate canning beans .in tomato sauce has been developed and compared to the commercial processing procedures with comparable results. External factors that influenced the canning quality like the water quality were investigated. This micro-canning method could therefore be used to investigate the effect of genotype and environment interactions that significantly influenced the canning quality. The objectives of this study were to: o Evaluate different qeriet i.c material for use as parents in the breeding program. $ To obtain a better understanding of canning quality characteristics of beans and to ensure that the most important characteristics are evaluated and the component interrelationships. • Determine the genotypic, environmental and genotype x environment interactions that influenced the canning quality. • To ascertain the patterns of interrelationships of the canning quality parameters and chemical analysis. • To investigate the patterns and relationships between standard and choice grade cultivars. e To investigate stability of locali ties between seasons as well as the clustering of different environments and seasons. Small seeded white beans, carioca and yellow haricot beans were used to determine variability in canning quality but as a result of a lower canning quality of coloured beans, only small seeded white beans were used for further investigations. As result of the investigations of different a characteristics, only the seed size, water absorption during soaking and canning, the texture and subjective visual appearance evaluations were used to determine canning quality. These characteristics were interrelated but single no parameter could explain variation' in canning quality. Canonical correlation analysis was used to determine to what extent variation of chemical components was responsible for differences in canning quality and these results indicated that mainly potassium and calcium would influence the water absorption and texture, respectively. Canonical variate analysis was used to determine the difference between unacceptable, standard and choice grade cultivars. A model was described from these analysis that could be applied to independent data sets that results in coordinates that differentiates the lines or cultivars as unacceptable, standard and choice grade. Significant interactions between genotype, environmental and seasonal effects for canning quality traits indicated that cultivar responses to variation in localities and seasons differ. Environmental effects resulted in inconsistent quality measurements since trait expression is strongly influenced by genotype x environment interactions. Results from this study suggested that the difference between cultivars could therefore be due to a complex interaction of the chemical and structural composition, which is genetically determined and influenced by the anv i ronmen t . as well as the changes that occur during processing. The Additive Main Effects and Multiplicative Interaction (AMMI) model mainly grouped KwaZulu-Natal separately as a region with poor canning quality. The rest of South Africa's localities grouped different for each season. Resulting from this investigation, several recommendations can be made: c Breeding material should be tested fo~ more than one season in order to select superior and more stable lines. o Elimination of canning quality evaluations of KwaZulu-Natal could improve the genetic progress. • Exploitation of the interactions by breeding for specific adaptation in a region of homogeneous area. Demarcating one or two areas in South Africa for the exclusive production of small white canning beans could improve the overall canning quality of the small white bean production in South Africa.

Dit is belangrik vir die produsente, prosesseerders en verbruikers in Suid-Afrika om droëboon kultivars met 'n aanvaarbare inmaakkwaliteit tot hulle beskiking te hê. Die droëboonteler moet dus verskillende lyne in die teelprogram reeds in 'n vroeë staduim toets wanneer slegs klein hoeveelhede saad beskikbaar is. 'n Mikro-inmaakmetode om kleinsadige wit bone in tamatiesous te toets is ontwikkel en vergelyk met die kommersiële prosesserings metodes met aanvaarbare resultate. Eksterne faktore wat die inmaakkwaliteit beïnvloed soos die water kwaliteit is ook ondersoek. Die mikro-inmaakmetode is dus gebruik om die effek van die genotipe en omgewings interaksies wat die inmaak kwaliteit betekenisvol beïnvloed te ondersoek. Die doel van hierdie studie was om: ~ Genetiese materiaal te evalueer vir die gebruik in die teelprogram as ouers. e Inmaakkwali teits eienskappe van die bone te ondersoek om sodoende te verseker dat net die belangrikste eienskappe geëvalueer word en om vas te stel wat is interverwantskappe. die • Genetiese, omgewings en die genetiese en omgewings interaksies wat die inmaakkwaliteit beïnvloed te bepaal. • Om te bepaal wat is die interverwantskappe tussen die inmaakkwaliteit en die chemiese komponente. • Om die tendense en verwantskappe tussen standaard- en keurgraad cultivars sowel as die onaanvaarbare cultivars te bepaal. • 'n Ondersoek na die stabiliteit van lokaliteite van siesoen tot seisoen asook die groeperinge van verskillende omgewings en seisoene te bepaal. Klein wit inmaakbone, carioca en geel haricot bone is gebruik om variëteit se inmaakkwaliteit te bepaal maar as gevolg van 'n swak inmaakkwaliteit van die gekleurde bone is besluit dat verdere ondersoeke slegs op die wit bone gedoen sal word. As 'n resultaat van die navorsing van verskillende eienskappe is slegs die saadgrootte, waterabsorpsie gedurende week en die tekstuur en 'n subjektiewe visuele voorkoms evaluering gebruik vir die bepaling van inmaakkwaliteit. Hierdie eienskappe is verwant aan mekaar maar daar is nie een parameter wat die variasie in inmaakkwlai tei t kan definieer nie. Kanoniese korrelasie analise is gebruik om vas te stel tot watter mate die chemiese komponente verantwoordelik was vir die verskille inmaakkwaliteit en hierdie resultate het aangedui dat kaluim en kalsuim die water absorpsie en tekstuur, repektiewelik, beïnvloed. Kanoniese veranderlike analise is gebruik om die verskille tussen onaanvaarbare, standaard en keurgraad cultivars te ondersoek. 'n Model is bereken sodat onafhanklike koordi na t e bereken kan word om sodoende die cultivar as keurgraad, standaardgraad of onaanvaarbaar te klassifiseer. Betekenisvolle interaksies tussen genotipe, omgewings en jaar effekte vir inmaakkwaliteits eieskappe het getoon dat cultivar reaksies op veranderinge in die omgewings en seisoene verskil. Omgewingseffekte veroorsaak onstabiliteit in inmaakkwalitet aangesien uitdrukking van sekere genetiese eienskappe baie beïnvloed word deur die genetiese en omgewings interaksies. Resultate van hierdie studie dui dus daarop dat die verskille tussen die inmaakkwaliteit van die cultivars 'n komplekse interaksie is van die chemiese en strukturele samestelling wat genetiese bepaal word, maar deur die omgewing beïnvloed word, sowel as veranderinge wat gedurende prosessering voorkom. Die AMMI model ("Addi tive Main Effects and Multiplicative Interaction") het hoofsaaklik getoon dat KwaZulu-Natal apart groepeer met 'n deurgaans swak kwali tei t. Die res van Suid- Afrika se lokaliteite groepeer saam. Lokaliteite vir 'n spesifieke eienskappe. seisoen kan ook saam groepeer vir sekere Vanuit hierdie studie kan dus aanbeveel word dat: • Die teelprogram se materiaal vir meer as een seisoen getoets moet word om die goeie en stabiële cul tivars te verkry. o Die illiuaakkwaliteit evaluerings vir die KwaZulu-Natal gebied uitgelaat moet word om sodoende genetiese vordering te versnel. o Die interaksies wat die inmaakkwaliteit beïnvloed moet tot voordeel van die teelprogram gebruik word deur cultivars te kry wat vir spesifieke homogene areas aangepas is. o Ten einde die omgewingsinteraksies uit te skakel kan sekere homoge~e areas in Suid-Afrika gekies word vir die produksie van kleinsadige wit cuitivar spesifiek vir die gebruik as inmaak bone om sodoende te verseker dat die prosesserders altyd g·:)eiekwali tei t inmaakbone tot hulle beskikking het en die produsente goeie pryse ontvang vir hulle produkte.
Thesis (Ph.D. (Food Science))--University of the Free State, 1999
Keywords: Drybeans; Small seeded white beans; Canning quality; Microcanning method; GxE interactions; Principal components; Canonical correlations; Canonical variate analysis; AMMI analysis; Common bean -- Preservation; Common bean -- Quality; Canning and preserving